Some Properties of Y3-8-11/Y211 Composite Bulk Superconductors - Kruaehong*, Thitipong; Sujinnapram, Supphadate; Nilkamjon, Tunyanop; Ratreng, Sermsuk; Udomsamuthirun, Pongkaew (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2018)
In this research, we investigated the properties of Y3-8-11 superconductor formed by the mixing of the non-superconducting Y211 material and Y3-8-11 at several contents. The critical temperature, XRD and DTA were measured. The Y3-8-11 and Y3-8-11/Y211 superconductors were synthesized using solid state reaction. We found that the Y3-8-11 superconductor showed the same property as Y123 except the lattice parameter in c-direction and DTA spectra. The lattice parameter c/a ratio of Y123 and Y3-8-11 were 3.06 and 9.15, respectively. The Y3-8-11 showed two peritectic phases but Y123 has one peritectic phase. The more non-superconducting composition, the lower value of c direction of Y3-8-11 was found. As Y211 composition increasing, the critical temperature decreased. Keywords: Y-based superconductor, Solid state reaction, Y211 Email: kruaehong@hotmail.com